The importance of local food products attributes in Brazil consumer's preferences - Suzi Cristiny da Costa Marques; Juliana Rosa Carrijo Mauad; Carla Heloisa de Faria Domingues; João Augusto Rossi Borges; Juliano Rosa da Silva (Future Foods, 2022)
The consumption of local food products is a trend in several countries. Governments have developed strategies to stimulate the production and consumption of local food products, which in turn might empower the local economy. This study aimed to identify the importance of local food products attributes in Brazil. An online survey was conducted, and a dual-response Best-worst scaling method was applied to sample of 205 Brazilian consumers. Results of the Hierarchical Bayes analyses showed that the order from the most to the least important attributes were: (1) Healthiness, (2) Safety, (3) Animal welfare, (4) Environmental impact, (5) Support of the local economy, (6) Taste, (7) Price, (8) Availability, (9) Traceability, (10) Place of origin, (11) Convenience. Based on the results, managerial implications are presented.